(untitled) (Research, Society and Development, 2021)
Introduction: Prostate cancer (PC) is the second most diagnosed in the male population in the world. Clinically, PC is subdivided into primary cancer, castration-resistant metastatic prostate cancer, and neuroendocrine prostate cancer. Objective: to describe the main molecular changes necessary for the development of primary prostate cancer (PCa). Methodology: this is a descriptive literature review. The databases PUBMED, SCIELO, Science Direct and Academic Google and National Cancer Institute (INCA) were used. The inclusion/exclusion criteria were articles from 2015 to 2021, available in Portuguese, English and Spanish. Results and discussion: the molecular bases of PC present several genomic alterations such as mutations, alterations in the number of copies of DNA, rearrangements and gene fusions. For primary cancer, the most prevalent genetic alterations are alterations in the ETS family genes such as ERG gene fusions (which occur in 50% of cases and mutations mainly in the CHD1, SPOP and BRCA1 or BRCA2 genes). In castration-resistant metastatic prostate cancer, the most prevalent genetic alteration alters androgen receptors and oncosuppressors (e.g. PTEN and TP53). Conclusion: alterations in genetic and epigenetic levels in specific genes regulated by androgen hormones are closely related to the pathogenesis of PC. These data are of paramount importance for understanding the pathophysiological mechanism of this condition, as well as providing the basis for a more specific treatment.